Happiness and the role of communication students at the University of Guayaquil - Jiménez Correa, Tanya Johanna; Flores Quinde, Josué Jonathan (Scripta Mundi, 2023)
The present research approaches the topic of happiness and the role of the students of the Faculty of Social Communication of the University of Guayaquil, Facso. The methodological approach applied is of a mixed, descriptive and non-experimental design, the survey was used as a technique and the questionnaire and bibliographic review as instruments. This allowed to analyze in the discussion and results that it is evident that the variable happiness is a feeling that human beings desire, in relation to the role as a student they consider that each individual interprets it at his/her convenience and that there is a correlation between happiness and the academic result and this allows them to be satisfied fulfilling their goals. In conclusion, this research is a contribution to the scientific and university community, since it is very important to investigate the feelings of students in order to enhance their role as learners and as a consequence obtain an optimal academic performance and in the future be good professionals.